Psychometric Properties of the Persian Version of Sickness Impact Profile-30 (SIP-30) in Community-Dwelling Older Adults - Sajad Siavash; Amin Ghaffari; Ghorban Taghizadeh; Laleh Lajevardi; Akram Azad (Journal of Aging Research, 2025)
Conclusions: The results indicated that the Persian SIP-30 is a reliable and valid measure to assess health-related quality of life in community-dwelling older adults.